ANALISIS KAPABILITAS TEKNOLOGI INFORMASI DAN PEMASARAN DIGITAL TERHADAP KEUNGGULAN BERSAING - Muhammad Taufik Ibrahim; R Deni Muhammad Danial; Kokom Komariah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
This study aims to determine the description of Information Technology Capability and Digital Marketing on the Competitive Advantages of UMKM Bakery and Pastry in Sukabumi City, to know Information Technology Capabilities to Competitive Advantages, to Know Digital Marketing to Competitive Advantages. The results in this study using the coefficient of determination test seen from the value (R Squire) that the effect of Information Technology Capability and Digital Marketing on Competitive Advantage is 0.653, while Information Technology Capability on Competitive Advantage is 0.718 The amount of Digital Marketing on Competitive Advantage is 0.743 the effect of Information Technology Capability and Digital Marketing on Competitive Advantage 65.3% and the remaining 34.7% is influenced by other variables not examined. From the results obtained from the hypothesis test (F test) it can be seen that Information Technology Capability affects Competitive Advantage and Digital Marketing influences Competitive Advantage. The results of the partial hypothesis test (T test) show that Information Technology Capability has a significant positive effect on Competitive Advantage and Digital Marketing has a significant positive effect on Competitive Advantage.